2014
DOI: 10.5604/20831862.1099372
|View full text |Cite
|
Sign up to set email alerts
|

NO ASSOCIATION BETWEEN tHbmass AND POLYMORPHISMS IN THE HBB GENE IN ENDURANCE ATHLETES

Abstract: The aim of this study was to examine the association between tHbmass and HBB gene polymorphisms in athletes of endurance disciplines. Eighty-two well-trained athletes (female n=36, male n=46), aged 19.3 ± 2.7 years, representing cross country skiing (n=37) and middle- and long-distance running (n=45), participated in the study. Genotyping for 2 polymorphisms in the HBB gene (- 551C/T and intron 2, +16 C/G) was performed using restriction fragment length polymorphism analysis. Total haemoglobin mass (tHbmass) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The maintenance of such a high value despite drastically reduced training intensity/volume points to the potential importance of genetic determinants for high Hb mass . However, thus far the search for gene polymorphisms to explain variations in Hb mass in athletes have failed (72). While augmenting red blood cell volume by means of blood transfusions or erythropoietin injections improves exercise performance in healthy humans (13,70,100), published data on elite athletes do not exist.…”
Section: How and By How Muchmentioning
confidence: 98%
“…The maintenance of such a high value despite drastically reduced training intensity/volume points to the potential importance of genetic determinants for high Hb mass . However, thus far the search for gene polymorphisms to explain variations in Hb mass in athletes have failed (72). While augmenting red blood cell volume by means of blood transfusions or erythropoietin injections improves exercise performance in healthy humans (13,70,100), published data on elite athletes do not exist.…”
Section: How and By How Muchmentioning
confidence: 98%
“…To the best of our knowledge, this is also the first study to show that intron rs1572312:C>A polymorphism of the NFIA-AS2 gene in male cyclists was associated with relative values of tHbmass, EV as well as with BV and PV. The relationship between genes and tHbmass was analyzed in previous studies, but it was related to 2 HBB gene polymorphisms and did not confirm such a relationship (20,21). Simultaneously, it is worth noting that we did not observe an association between CC genotype of the NFIA-AS2 gene and basic blood morphology indices, such as hemoglobin concentration, red blood cell count, and hematocrit.…”
Section: Discussionmentioning
confidence: 96%
“…It was also shown that tHbmass correlates more strongly than Hb with indices of exercise capacity (6,29). However, so far, researchers have examined only 2 polymorphisms of the HBB gene (responsible for beta-globin synthesis in the hemoglobin molecule) for their impact on tHbmass or physical capacity in athletes (20,21). Unfortunately, the results of both studies did not confirm the association between tHbmass and the HBB gene.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the DNA samples was validated by amplification of a 110-bp fragment of the hemoglobin beta-chain )HBB) gene. [19] Infection with HPV was examined by PCR amplification with HPV-specific DNA sequences. This step used a universal HPV primer pair (“consensus primer”) which was specific for HPV 16.…”
Section: Methodsmentioning
confidence: 99%